Preparedness for peer first response to mining emergencies resulting in injuries: a cross-sectional study - Sofia Karlsson; Magnus Hultin; Britt-Inger Saveman; Ulf Björnstig; Lina Gyllencreutz (BMJ Open)
Objective Identify factors of preparedness for peer first response to underground mining emergencies with injured victims.Design Cross-sectional questionnaire study of Swedish underground mineworkers.Setting Seven out of nine Swedish underground mines.Participants A total of 741 mineworkers out of 1022 (73%) participated in this study.Interventions None.Outcome measures Level of preparedness for emergencies with injuries in underground mines.Results Three factors influenced the preparedness of mineworkers for a peer first response: (1) familiarity with rescue procedures during emergencies with injuries; (2) risk perception of emergencies with injuries and (3) experience of using self-protective and first aid equipment. Mineworkers who believed that they knew how to handle emergencies with injuries (OR 1.30, 95% CI 1.22 to 1.38) and those who were trained in the use of self-protective and first aid equipment (OR 1.19, 95% CI 1.07 to 1.32) considered themselves to be better prepared for a peer first response than those who were unfamiliar with the rescue procedures or who had not used self-protective and first aid equipment. However, mineworkers who rated the risk for emergencies with injuries as high considered themselves to be less prepared than those who rated the risk as low (OR 0.95, 95% CI 0.91 to 0.98).Conclusion This study identified three factors that were important for the peer-support preparedness of underground mineworkers. More research is needed to adapt and contextualise first aid courses to the needs of underground peer responders.